Mental Models and Dynamic Capabilities in a Brazilian Family Company - Rubens Mussolin Massa (FUCAPE Business School, 2020)
This article analyzes how the concepts of paradigm, organizational culture, and cognition of resources influence the mindset of managers and skew the choice of which dynamic capabilities should be developed by an organization, in the process of innovation and change. A case study was carried out that examined a traditional 64-year-old family publishing house. In-depth interviews with the company’s partners were conducted, as well as a documental analysis. The results revealed that organizational paradigms skew the choice of which dynamic capabilities should be developed, prioritizing those that are in accordance with the organizational paradigm. Therefore, the organization tends to be aligned with its own paradigm, rather than aligning with context. It demonstrates the importance of the organizational paradigm, organizational culture, and cognition of resources in the mindset of managers. Throughout periods of innovation and change, those aspects may influence the decision-making process in the organization. This is considered a relevant aspect of understanding how some small businesses survive environmental changes while others succumb to them.